2009
DOI: 10.1590/s1516-31802009000300012
|View full text |Cite
|
Sign up to set email alerts
|

Hemosiderotic fibrohistiocytic lipomatous lesion: case report and review of the literature

Abstract: We describe the case of a 33-year-old female patient with a soft-tissue lesion in her left knee that was diagnosed as a hemosiderotic fibrohistiocytic lipomatous lesion. This type of lesion, which was described for the first time in 2000, preferentially affects the ankle region of middle-aged women with a history of previous local trauma. Lesion recurrence is common, caused by incomplete resection, although there have not yet been any reports of metastases. After a review of the literature, we describe the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Luzar et al [9] 2006 1 Female 47 Ankle 1.9x1.2 cm West et al [10] 2007 1 Female 38 Foot NA de Vreeze et al [11] 2008 1 Male 66 Thigh 19x8x4 cm Wettach et al [12] 2008 1 Female 35 Foot NA Hallor et al [13] 2008 1 Female 40 Ankle NA Ramalho et al [14] 2009 1 Female 33 Knee 10x8x6 cm Moretti et al [15] 2010 1 Female 56 Foot 7x5x2 cm Antonescu et al [2] 2011 14 2 -Male 12 -Female 45 13 -Foot 1 -Hand NA Sawalha Setal. [3] 2011 1 Female 55 Hand 3x1 cm Carter et al [4] 2014 Marusic Z et al [16] 2014 1 Female 57 Ankle 15x5 cm Zreik et al [17] 2016 1 Female 77 Foot NA Morency et al [18] 2016 1 Female 55 Foot 3x1 cm Wilk et al [19] 2016 1 Female 45 Foot 14x6 cm Etchebehere et al [20] 2016 1 Female 38 Thigh 22x18x11cm Hou et al [21] 2018 1 Male 50 Knee joint 4x2.5x1.9cm Bourhroum N et al [22] 2019 1 Female 50 Ankle 7 cm Pang CY et al [6] 2021 and Fanburg -Smith.…”
Section: Discussionmentioning
confidence: 99%
“…Luzar et al [9] 2006 1 Female 47 Ankle 1.9x1.2 cm West et al [10] 2007 1 Female 38 Foot NA de Vreeze et al [11] 2008 1 Male 66 Thigh 19x8x4 cm Wettach et al [12] 2008 1 Female 35 Foot NA Hallor et al [13] 2008 1 Female 40 Ankle NA Ramalho et al [14] 2009 1 Female 33 Knee 10x8x6 cm Moretti et al [15] 2010 1 Female 56 Foot 7x5x2 cm Antonescu et al [2] 2011 14 2 -Male 12 -Female 45 13 -Foot 1 -Hand NA Sawalha Setal. [3] 2011 1 Female 55 Hand 3x1 cm Carter et al [4] 2014 Marusic Z et al [16] 2014 1 Female 57 Ankle 15x5 cm Zreik et al [17] 2016 1 Female 77 Foot NA Morency et al [18] 2016 1 Female 55 Foot 3x1 cm Wilk et al [19] 2016 1 Female 45 Foot 14x6 cm Etchebehere et al [20] 2016 1 Female 38 Thigh 22x18x11cm Hou et al [21] 2018 1 Male 50 Knee joint 4x2.5x1.9cm Bourhroum N et al [22] 2019 1 Female 50 Ankle 7 cm Pang CY et al [6] 2021 and Fanburg -Smith.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have concluded that HFLT, PHAT, and MIFS represent morphologic variants of a single entity, in which only the later has acquired the capacity to metastasize 3, 8, 9. One histological study suggested that most, if not all, tumors diagnosed as PHATs might actually represent examples of MIFS with aberrant angiectatic hyalinized vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we report a published case of a lesion that had previously been diagnosed, according to its morphological and by immunohistochemical (IHC) features, as HFLT 8 . The lesion recurred twice and later showed malignant transformation to a low-grade unclassified pleomorphic sarcoma, with an IHC study suggesting myofibroblastic differentiation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation